The Comparative Toxicity of 10 Microcystin Congeners Administered Orally to Mice: Clinical Effects and Organ Toxicity - Neil Chernoff; Donna Hill; Johnsie Lang; Judy Schmid; Thao Le; Amy Farthing; Hwa Huang (Toxins, 2020)
Microcystins (MCs) are common cyanobacterial toxins that occur in freshwaters worldwide. Only two of the >200 MC variants have been tested for potential toxicity after oral exposure. This paper reports on the toxicity of 10 different MC congeners identified in algal blooms, microcystin-LR (MCLR), MCLA, MCLF, MCLW, MCLY, MCRR, [Asp3]MCRR, [Asp3,Dhb7]MCRR, MCWR, and MCYR after single administrations to BALB/c mice. In a preliminary MCLR dose–response study of 3 to 9 mg/kg doses, ≥5 mg/kg induced clinical changes, increased serum levels of ALT, AST, and GLDH, liver congestion, increased liver/body weight ratios, and reduced serum glucose and total protein. Based on the extent of these effects, the 10 congeners were administered as single 7 mg/kg oral doses and toxicity evaluated. The greatest toxicity was observed with MCLA and MCLR including a high percentage of moribundity. In addition to eliciting effects similar to those listed above for MCLR, MCLA also induced serum alterations indicative of jaundice. MCLY, and MCYR induced changes like those noted with MCLR, but to lesser extents. MCLW and MCLF exhibited some serum and morphological changes associated with hepatic toxicity, while there were few indications of toxicity after exposures to MCRR, [Asp3]MCRR, [Asp3,Dhb7]MCRR, or MCWR. These data illustrate a wide spectrum of hepatic effects and different potencies of these MC congeners.